Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2025)
Table of Content:• The Effectiveness of Using Gamification Strategy in Enhancing the Motivation of Business Administration Students to Learn the Principles of Financial Management Course in Saudi ArabiaDr. Razaz Houssien Felimban• The Strategic Rivalry Between Turkey and Iran and Its Implications for the Middle EastMr. Ali Khidr Matar• The modern management accounting methods and their relationship to achieving  the competitive advantage of business organizations A field study of the industrial sector in Hafar Al-Batin(2020-2025)Co-Prof. Noureldaim Eltayeb Yousif Elhag• The Russia–Ukraine War and the Struggle to Shape the New International OrderMr. Kamal Kamel Tarhini• Subcontracting: A Study in the Framework of Administrative Contracts Under the Saudi SystemMr. Abdulrahman Abdulaziz Ibrahim Al-Mohana• Corporate Governance Practices and Their Contribution to Achieving Saudi Arabia’s Vision 2030 Objectives: An Applied Study on Emerging Cybersecurity CompaniesMr. Mohammad Abdulaziz Alduriweesh• The impact of using the balanced scorecard on the organization's strategic planning  (An applied study on the Ministry of Social Development)Prof. Sulaiman Hussein Al-Muzain, Mr. Muhammad Ishaq Al-Salti• Credit Risk Analysis and Its Impact on Financial Performance Indicators Based on Accounting Profit: An Applied Study on Saudi Stock Exchange Institutions During the period 2018 – 2022Co-Prof. Alsadig Mohamed Salim
Keywords: The Journal of Economic, Administrative and Legal Sciences